Police culture, transparency and civilian oversight: A case study of the National City Police Department - Triola, Anthony M (International journal of police science & management, 2023)
The aim of this article is to take stock of theorizing around the concept of police culture, the degree to which it may be static or dynamic, and the ways in which these collectively shared practices and ideals influence and are influenced by social structural problems. We take a “ground-up” approach to this problem by conducting interviews with officers and staff from a relatively small Southern California police department (National City Police Department). The interviews were aimed at gauging officer opinions on the issues of civilian oversight and departmental transparency. These were conducted using Q-sorts, which prompt the interviewee to rank order responses to the questions. These answers were subjected to exploratory factor analysis, the function of which is to take steps towards ascertaining latent causal relationships that underlie correlational relationships. The inductive nature of this methodological approach limits its generalizability but allows for exploration into open-ended questions that can serve as bases for the expansion or refashioning of theoretical approaches. Overall, our findings suggest a need for further exploration into the extent to which demographic and experiential characteristics may underlie a more diversified police occupational culture than the traditional police culture narrative suggests.